Bears - Krauss, Ruth (HarperCollins, 2005)
With just 27 words, the inimitable Ruth Krauss created a charming little universe. Now Maurice Sendak has turned her bears into a troupe of players in a slapstick comedy starring a familiar boy in a wolf suit. With just 27 words, the inimitable Ruth Krauss created a charming little universe. Now Maurice Sendak has turned her bears into a troupe of players in a slapstick comedy starring a familiar boy in a wolf suit.